(untitled) (MAUSAM, 1983)
The response of the upper oceanic subsurface thermal structure to the summer monsoonal forcing over Bay of Bengal in the temporal domain of May, June and July of 1979 at selected stationary ship positions has been investigated with the aid of surface marine meteorological and bathythermograph data collected during MONEX-79. Forcing of a severe pre-monsoon cyclonic storm on the ocean surface mixed layer characteristics is documented. Surface heat exchange components, vertical thermal gradient just below mixed layer are made use of to explain the observed variability in the surface mixed layer characteristics. Depth-time fields of temperature of the upper 200 m water column are analysed and discussed.